PENGEMBANGAN MODUL BERBASIS KONSTRUKTIVISME DENGAN TAMPILAN MAJALAH UNTUK MATERI PERBANDINGAN PADA PEMBELAJARAN MATEMATIKA SISWA KELAS VII SMPN 13 PADANG - Sari, franica - (STKIP PGRI Sumbar, 2014)
A textbook has not been able to facilitate the students to studyÂ independently and made theÂ student aesy to construct the concept of math well.The txtbook layout is also not interesting so that the students are not interested to study about it. Therefore, the research aims to develop a valid and praticical constructivism-based modyle with the magazine layout for the comparison mateerial at public Junior High School 13 Padang.The research is adevelopment research using Plomp design.It is conducted through two stages,i.e. 1) preliminery research and 2)prototyping phase with the formative evaluation method chosen is self-evaluation,expert review,and one-to-one evaluation.The types of collected data on this research are quantitative and qualitativeÂ data.The module validity analysis result, which is based on 4 aspects, i.e.content appropriateness,material presentation,linguistic,and graph,is very valid and appropriate to use.The rasult of practical analysis shwos that the module is practical to use in learning.